RELATIONS OF pH AND SEDIMENT ORGANIC MATTER CONTAINS TO MANGROVE VEGETATION REVENUE IN REGENCY OF NORTH RUPAT REGENCY OF BENGKALIS DISTRICT RIAU PROVINCE - Putra '; Irvina Nurrachmi; Joko Samiaji (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The research was conducted in January 2017 in the mangrove ecosystem of North Rupat Subdistrict, Bengkalis Regency, Riau Province. The purpose of this research was to observe the relationship between sediment pH and organic sediment content with the density of mangrove vegetation. The result of ANOVA test showed pH = 0, organic matter = 1.413 and mangrove density = 2.181 with probability value of 1, 0,314 and 0,194 (> 0,05) then the three variant of population of each variable are identical. Regression test showed the value of pH relationship of sediment and organic matter of sediment to mangrove density was at 0.67%. In the correlation test showed very weak / no significant influence of both parameters on mangrove density in North Rupat Sub-district, Bengkalis Regency, Riau Province.Keyword : pH, Organic Matter, Mangrove, North Rupat, Bengkalis